Creative Moves in Cimory's Milk Billboard Ads Targeting Young Adults and Adults: A Genre Analysis - Sunandar, Crystalina Malika; Darajat, Kurnia Fahma Zakia; Yulizar, Kessya; Syahriyani, Alfi (Insaniyat : Journal of Islam and Humanities, 2025)
As a recognized advertising medium, billboards serve as one of the strategic choices for companies to promote their products and convey their communicative purposes. Cimory Milk, a dairy brand, uses billboard advertisements in unique and creative ways to engage their target market. This is evident in how Cimory Milk billboard advertisement serves the unusual discourse by playing with the generic conventions of the advertisement genre. Thus, the creative ways are leading through some specific intention that Cimory Milk tries to convey, which is related to the adults and youth discourse community. To explore this, the present study employs a qualitative approach, drawing on Bhatia’s genre analysis and Kress & Leeuwen’s multimodal discourse analysis. Using these frameworks, three Cimory Milk billboard advertisements were analyzed in terms of their moves, creative elements, and the relationship between creativity and audience engagement. This study found that although Cimory billboard advertisements adhered to the general conventions of the advertising genre, some creative strategies such as bending and blending were evident in the advertisement. These creative elements are designed to attract young adults to adults, through features such as the minimalist design, humor, strategic placement, and references to social and lifestyle issues. Overall, the result of this study illustrates how Cimory Billboard analysis uses creativity to engage young adults and adults as their target consumers. These findings may also offer valuable insight for advertisers to identify consumer’s perceptions and improve their marketing strategy.